Indigenous music in healing rituals : a comparative study of the Twelve Apostles Church in Ghana and shamanism in Finland - Asare, Amos Darkwa (Taideyliopiston Sibelius-Akatemia, 2015)
The study describes and analyzes the use of indigenous music in the healing rituals of the syncretic Twelve Apostles Church in Ghana and shamanism in Finland. In dealing with the main question of how indigenous music should be seen as an integral part of the healing processes of two geographically distant cultures, the thesis focuses on the cultural values, meanings and understandings of the participants. The basis of analysis lies beyond Western medical interpretations and extends to music- singing, drumming and dancing in indigenous or local healing rituals agreed upon by a definable set of people. This includes the people's beliefs, art, customs and norms. Thus, the thesis presents an ethnographic study of indigenous music in healing by comparing how the syncretic Twelve Apostles Church in Ghana and shamanism in Finland approach their healing rituals with music. The main methods employed are participant observations and interviews. The major finding is that indigenous healings are effective with musical phenomena making the ritual music, and music the ritual.
Keywords: šamanismi; rituaali; Ghana; Suomi; Glomas